Fish Species and Abundance in the Intertidal Zone around UNSRAT Marine Station, East Likupang District, North Minahasa Regency - Pangandaheng, Romel A.; Bataragoa, Nego E.; Tombokan, Jhon L. (Sam Ratulangi University, 2018)
Fish migration to the intertidal zone at high tide is for feeding, reproduction, escape from predator. The study was aimed to know the fish species inhabiting the intertidal zone, the individual abundance and fish catch biomass. Sampling was done at high tide in the afternoon and morning in new moon and full moon. Five sampling stations were selected and each station was sampled twice, so that total number of samplings were 10. This study used swept area method and covered a total area of 12,000/m2 (6,000m2 in new moon and full moon, respectively. Individual abundance of each species ranged from 0.0002 to 0.0120/ at new moon and from 0.00012 to 0.0102/ at full moon, respectively, and total abundance ranged from 0.0001 to 0.0111/ in both moon phases. The biomass of each species on the new moon 0.0003t o 0.1749g/ , full moon 0.0009 to 0.1224g/ , and the amount of biomass between the new moon and the full moon 0.0002 to 0,1329g/ .Keywords: Fish, migration, intertidal, reproduction.AbstrakIkan bermigrasi ke dalam zona intertidal pada saat air pasang adalah untuk mencari makan, bereproduksi, dan menghindar dari predator. Tujuan penelitian ini adalah untuk mengetahui spesies-spesies ikan yang ada didaerah intertidal dan mengetahui kelimpahan individu dan biomasa ikan yang tertangkap di daerah intertidal. Pengambilan sampel dilaksanakan pada ketika air pasang pada sore dan pagi hari setiap fase bulan baru dan purnama. Ditetapkan lima stasiun sampling dan setiap stasiun dilakukan dua kali sampling, sehingga jumlah sampling dalam lima stasiun 10 kali sampling. Dengan metode penelitian yang digunakan adalah metode swept area (daerah sapuan). Luas daerah sapuan pukat dalam 10 kali sampling adalah 12.000/m2 (6.000m2 pada bulan baru dan bulan purnama), Kelimpahan individu setiap spesies pada bulan baru berkisar antara 0,0002-0,0120/ , bulan purnama 0,00012-0,0102/ , dan jumlah kelimpahan antara bulan baru dan purnama 0,0001-0,0111/ . Kelimpahan biomasa setiap spesies yang paling melimpah pada bulan baru 0,0003-0,1749g/ , bulan purnama 0,0009-0,1224g/ , dan jumlah biomasa antara bulan baru dan purnama 0,0002-0,1329g/ ..Kata kunci : Ikan, bermigrasi, intertidal, reproduksi